STUDI MORFOLOGI FRACTURE SURFACE DENGAN HASIL SPOT WELDING - Nofriady Handra; Rio Ansuni (Jurnal Teknik Mesin (JTM), 2013)
This research background with the desire of knowledge about what exactly the author Spot Welding and is usually used in the automobile industry for the manufacture of body of a car, the purpose of this study was to determine the time to do a good press plate welding especially in Black and Galvanized plate with a thickness of 1.2 mm . The first method of research conducted test process composition, creation of test samples, perform welding with welding machine Spot Welding, further testing of tensile and shear on each - each plate type, data processing, data analysis form conclusions, and report generation. After doing the research and the results obtained, a good press time at 3.5 seconds on each plate with the current 26 Ampere, it is evident after tensile test on galvanized plate and black plate worth gained the greatest diameter 4.3 mm for the black plate and for shear test galvanized plate and black plate valued largest diameter 5,35 mm for the black plate. From the above data it can be concluded that at the time of press time spot welding greatly affect the value of tensile and shear strength, in due time to the welding electrode material emphasis will generate heat, thus forming clumps, the resulting heat will affect the outcome of the weld .